2018
DOI: 10.1111/eea.12661
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Myzus persicae and transmission of Potato virus Y under elevated CO2 atmosphere

Abstract: Most phytoviruses use insect vectors to spread and infect the surrounding crop plants. Because atmospheric gas concentrations alter the physiology and metabolism of plants, we hypothesize that the concentration of carbon dioxide (CO 2 ) affects the spread of viruses, due to modifications in the feeding behavior of the vector. Tobacco plants, Nicotiana tabacum L. (Solanaceae), and green peach aphids, Myzus persicae (Sulzer) (Hemiptera: Aphididae), were cultivated under ambient (450 p.p.m., termed aCO 2 ) and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…By the end of this century, atmospheric CO 2 concentration and global temperature on Earth will increase [1], directly and indirectly altering plant, insect, and virus interactions, thus affecting ecosystems, agriculture, and food production [44]. To date, most of the research regarding the impact of climate change on plant-insect-pathogen interactions has been conducted on a single climate or atmospheric variable, mainly either temperature or CO 2 [13,14,47,48,66]. However, to create representative conditions of future climate, research approaches should include the responses of multitrophic systems to climate variables that will occur simultaneously [17,27,45].…”
Section: Discussionmentioning
confidence: 99%
“…By the end of this century, atmospheric CO 2 concentration and global temperature on Earth will increase [1], directly and indirectly altering plant, insect, and virus interactions, thus affecting ecosystems, agriculture, and food production [44]. To date, most of the research regarding the impact of climate change on plant-insect-pathogen interactions has been conducted on a single climate or atmospheric variable, mainly either temperature or CO 2 [13,14,47,48,66]. However, to create representative conditions of future climate, research approaches should include the responses of multitrophic systems to climate variables that will occur simultaneously [17,27,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, Bosquee et al . () suggested that the altered plant defenses or aphid feeding behavior may have increased the ability of M. persicae to transmit phytoviruses under elevated CO 2 conditions. Furthermore, Xie et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the results of Bosquee et al . () showed that the ability of Myzus persicae to spread PVY was unaffected by the level of CO 2 at short time frame and at different spatial scales. However, the same authors observed more efficient viral transmission under elevated CO 2 conditions, and it was suggested that the main reason was the altered plant defenses or changes in the feeding behavior of their vector.…”
Section: Introductionmentioning
confidence: 99%
“…However, different results were obtained in PVY transmission experiments realised under similar conditions. When PVY-infected tobacco plants and M. persicae aphids were placed under eCO 2 levels (800 ppm vs. 450 ppm), transmission efficiency increased [59]; however, no clear explanation for this increase was apparent.…”
Section: Impact Of Abiotic Stresses On Viral Transmissionmentioning
confidence: 92%